Variation in stable carbon (δ13C) and nitrogen (δ15N) isotope compositions along antlers of Qamanirjuaq caribou (Rangifer tarandus groenlandicus) - Matthew Brenning; Fred J. Longstaffe; Danielle Fraser (Ecology and Evolution, 2024)
Abstract Annual antler growth begins in the spring and is completed by late summer for male caribou (Rangifer tarandus groenlandicus) from the Qamanirjuaq herd (Nunavut, Canada), aligned with both the spring migration and a seasonal dietary shift. Antlers may provide a non‐lethal means of studying short‐ and long‐term changes in caribou ecology through incorporated isotopes of carbon (δ13C) and nitrogen (δ15N). We sampled the antlers of 12 male caribou from the Qamanirjuaq herd culled in September 1967. We predicted that serial sampling of antlers would reflect the known seasonal dietary change from lichen to grass‐like and shrub diet based on rumen contents from individuals culled during the same period. The δ13C and δ15N were analyzed in food sources and every 3 cm along each antler's length. The carbon isotope compositions of collagen (δ13Ccol) varied by ~0.5‰ among individuals and within antlers, while the carbon isotope compositions of antler bioapatite (δ13CCO3) increased by 1–1.5‰ from pedicle to tip. Values of δ15Ncol increased within antlers by 1–3‰ from pedicle to tip and varied by 3‰ among the individuals sampled. Antler collagen was lower in δ15Ncol by ~1‰ relative to bone collagen. Bayesian mixing models were conducted to test for changes in dietary proportions from antler isotope compositions. Mixing models did not indicate significant dietary shifts for any individual during antler formation, showing consistently mixed diets of fungi, horsetail, lichen, and woody plants. Increases in δ15Ncol in antler tissue could, therefore, correspond to subtle seasonal dietary changes and/or the physiological stress of antler tissue development.